The Influence of Education and Training, User Involvement in System Development Toward Accounting Information Systems Performance with Top Management Support as Intervening Variables (Case Study at Dinas Pertanian, Perikanan dan Pangan, Semarang District) - Kurniasari, Sera Novia; Widyarti, Maria Theresia Heni; Ciptaningtias, Arum Febriyanti (Applied Accounting and Management Review (AAMAR), 2024)
Abstract: This study aims to determine the effect of user education and training, and the application of users in system development on accounting information system performance by supporting top management as an intervening variable. The number of samples in this study was 30 respondents. Sampling using a purposive sampling technique. Validity and reliability tests were used to test research instruments. The classic assumption test uses the normality test, multicollinearity test, and heteroscedasticity test.   Testing the hypothesis using the F statistical test and T statistical test. The results showed that user education and training did not affect accounting information system performance, user involvement in system development had an effect on accounting information system performance, top management support had an effect on accounting information system performance, top management support was not able to mediate the significant effect of education and training on accounting information system performance and top management support was not able to mediate the significant influence of user involvement in system development on accounting information system performance. Keywords: User Education and Training, User Application in System Development, Top Management Support.